Chemical reaction dynamics. (27th November 2017) - Yang, Xueming; Clary, David C.; Neumark, Daniel M.
Abstract : Guest editors Xueming Yang, David Clary and Daniel Neumark introduce the chemical reaction dynamics themed issue of Chemical Society Reviews .